«No One Had Ever Asked Me». Testimonies of Minors as a Source for Historical Research in Colombia (2024)
The objective of this article is to analyze how the experiences of girls, boys, and adolescents in the context of the Colombian war have been received and incorporated into the institutional work of memory construction. The analysis is based on a review of reports produced by the Historical Memory Group of the National Commission for Reparation and Reconciliation and the National Center for Historical Memory. The article begins by highlighting the inadequacy of articulated language in capturing the childhood and youth experiences of violence. It then examines how the testimonies of children and adolescents have been included in institutional memory reports to determine the validity attributed to the knowledge these testimonies can provide. Finally, the article concludes that the experiences of suffering in childhood and adolescence are not adequately addressed in institutional memory work, and there is a form of epistemic injustice that diminishes the importance and centrality of these testimonies as sources of knowledge about recent Colombian violence.